Analysis of Precision and Stability Tests of the Doce Calibrator CRC-25R - Feni Eka Novitasari; Adrianus Inu Natalisanto; Devina Rayzy Perwitasari; Retno Zurma (Jurnal Inotera, 2024)
Dose calibrator is a measuring tool that is widely used in hospitals to determine radionuclide activity in nuclear medicine services. In determining this activity it has several factors; namely precision, accuracy and stability which is become depining factor of the tool suitability. The aim of this research is to determine the level of precision, accuracy and stability of the Capintec dose calibrator type CRC-25R with an I-131 source and a standar Cs-137 source at the Nuklear Medicine Installation of RSUD A.W. Sjahranie Hospital Samarinda. Data processing in this research was carried out using quantitative analysis tecnhniques, namely descriptive statistics. This analysis technique use primary data obtained from direct measurements of radionuclide activity. Data processing was carried out by measuring radionuclide activity, namely source I-131 and standard source Cs-137 of 0,1 ml using a Capintec type CRC-25R for 7 days. These results are visualized in the form of tables and graphs of precision, accuracy and stability tests from both source with predetermined limits. Base on this research, it can be concluded that if we look at the precision, accuracy, and stability test using I-131 source anda Cs-137 standard source on the Capintec type CRC-25R at A. W. Sjahranie Samarinda Hospital, it can be used to measure a constant source over a long periode of Long time.